1997
DOI: 10.1063/1.364353
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dark-line defect growth suppression in InxGa1−xAs/GaAs strained heterostructures

Abstract: Erratum: "X-ray reciprocal space mapping of dislocation-mediated strain relaxation during InGaAs/GaAs(001) epitaxial growth" [J.The driving force of ͗100͘ dark-line defect ͑DLD͒ climbing growth based on vacancy unsaturation is discussed. In In x Ga 1Ϫx As/GaAs strained structures, it is found that compressive strain can reduce the osmotic ͑climb͒ force and can suppress the climb of DLDs in ͗100͘ direction. The percentage of indium in In x Ga 1Ϫx As/GaAs strained heterostructures for the suppression of ͗100͘ DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…PCL can also be blended with cellulose derivatives and other polymers for manipulating the rate of drug release from the scaffold. There are some reports in blends of PCL and cellulose nitrate [22], cellulose butyric ester [23,24], cellulose acetate-butyrate [16,25], cellulose acetate [16,26,27], long-chain ester of cellulose [9], ethylcyanoethyl cellulose [28], methylcellulose [29], poly(3-hydroxybutyrate) [30,31], and other polymers such as chitin or its derivative [32].…”
Section: Introductionmentioning
confidence: 99%
“…PCL can also be blended with cellulose derivatives and other polymers for manipulating the rate of drug release from the scaffold. There are some reports in blends of PCL and cellulose nitrate [22], cellulose butyric ester [23,24], cellulose acetate-butyrate [16,25], cellulose acetate [16,26,27], long-chain ester of cellulose [9], ethylcyanoethyl cellulose [28], methylcellulose [29], poly(3-hydroxybutyrate) [30,31], and other polymers such as chitin or its derivative [32].…”
Section: Introductionmentioning
confidence: 99%
“…Although the limited magnification available and the opaque p-metallizaiton layer prohibited direct EL observation of individual dark line propagation in the active laser cavities, the observed dark bands and their relatively rapid spreading through the operating devices matches the well-known behavior of DLDs in GaAs/AlGaAs lasers. 16,22,23 Control devices fabricated on GaAs substrates with otherwise identical laser characteristics did not show similar degradation behavior, indicating that differences in substrate material, and in particular the increased threading dislocation density in Ge/GeSi/Si, is most likely responsible for the shortened lifetimes on these substrates.…”
Section: Discussionmentioning
confidence: 54%
“…15 Work on GaAs substrates has shown that In x Ga (1Ϫx) As strained quantum well laser structures can resist dark line defect propagation, making such structures ideal candidates for integration on Ge/ GeSi/Si substrates. 16 Unfortunately, initial attempts to introduce In x Ga (1Ϫx) As strained quantum well layers on Ge/ GeSi/Si substrates led to misfit dislocation formation in the quantum well active regions. 17 In this work, we investigated improved growth and fabrication processes to address the integration challenges discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…People also have taken the idea of using indium to pin dislocations and worked for long periods on ill-fated projects that use just a few percent indium (papers were published with as little as a twentieth of a percent indium). Such low-compressive-strain lasers are not markedly superior to unstrained lasers, as experimentally observed by Waters et al The most plausible explanation for the dislocation pinning was offered by Wang, Hopgood, and Ng [8]. They argue that when the compressive strain exceeds the osmotic force of the point defects, dislocation pinning is possible.…”
Section: Categorymentioning
confidence: 87%